Advances in mechanical weed control technologies - Melander, Bo (Burleigh Dodds Series in Agricultural Science, 2021)
Mechanical weed control can be grouped into three categories: full-width cultivators, inter-row cultivators and intra-row cultivators. This chapter will highlight the most recent and relevant advances within each category. The focus will be on novel inventions and developments of mechanical devices, designs, and the weed problems they are meant to solve. Moreover, automation technologies that assist weeding operations are becoming increasingly important and will be given special attention.